Saving the news why the Constitution calls for government action to preserve freedom of speech - Minow, Martha 1954- (New York, NY Oxford University Press, 2021)
As traditional for-profit news media in the United States declines in economic viability and sheer numbers of outlets and staff, what does and what should the constitutional guarantee of freedom of the press mean? The book examines the current news ecosystem in the U.S. and chronicles historical developments in government involvement in shaping the industry. It argues that initiatives by the government and by private-sector actors are not only permitted but called for as transformations in technology, economics, and communications jeopardize the production and distribution of and trust in news and the very existence of local news reporting. It presents ten proposals for change to help preserve the free press essential to our democratic society"--
News deserts, echo chambers, algorithmic editors, and the siren call of revenues -- News production and distribution in the United States : private industry and government contributions -- Does the First Amendment forbid, permit, or require government support of news industries? -- Constitutionally inflected reforms -- CODA..
Includes bibliographical references and index.
Keywords: Freedom of the press -- Electronic book -- United States; Press law -- Economic aspects -- United States